Premature Discontinuation of Randomized Trials in Critical and Emergency Care: A Retrospective Cohort Study. Issue 1 (January 2016) - Schandelmaier, Stefan; von Elm, Erik; You, John J.; Blümle, Anette; Tomonaga, Yuki; Lamontagne, Francois; Saccilotto, Ramon; Amstutz, Alain; Bengough, Theresa; Meerpohl, Joerg J.; Stegert, Mihaela; Olu, Kelechi K.; et al.
Abstract : Objectives: Randomized clinical trials that enroll patients in critical or emergency care (acute care) setting are challenging because of narrow time windows for recruitment and the inability of many patients to provide informed consent. To assess the extent that recruitment challenges lead to randomized clinical trial discontinuation, we compared the discontinuation of acute care and nonacute care randomized clinical trials. Design: Retrospective cohort of 894 randomized clinical trials approved by six institutional review boards in Switzerland, Germany, and Canada between 2000 and 2003. Setting: Randomized clinical trials involving patients in an acute or nonacute care setting. Subjects and Interventions: We recorded trial characteristics, self-reported trial discontinuation, and self-reported reasons for discontinuation from protocols, corresponding publications, institutional review board files, and a survey of investigators. Measurements and Main Results: Of 894 randomized clinical trials, 64 (7%) were acute care randomized clinical trials (29 critical care and 35 emergency care). Compared with the 830 nonacute care randomized clinical trials, acute care randomized clinical trials were more frequently discontinued (28 of 64, 44% vs 221 of 830, 27%; p = 0.004). Slow recruitment was the most frequent reason for discontinuation, both in acute care (13 of 64, 20%) and in nonacute care randomized clinical trials (7 of 64, 11%). Logistic regression analyses suggested the acute care setting as an independent risk factor for randomized clinical trial discontinuation specifically as a result of slow recruitment (odds ratio, 4.00; 95% CI, 1.72–9.31) after adjusting for other established risk factors, including nonindustry sponsorship and small sample size. Conclusions: Acute care randomized clinical trials are more vulnerable to premature discontinuation than nonacute care randomized clinical trials and have an approximately four-fold higher risk of discontinuation due to slow recruitment. These results highlight the need for strategies to reliably prevent and resolve slow patient recruitment in randomized clinical trials conducted in the critical and emergency care setting. Abstract : Supplemental Digital Content is available in the text.